TABOO WORDS AND THEIR FUNCTIONS IN THE BAD BOYS FOR LIFE MOVIE - Muhammad Dimas Arbi Setyawan; Suci Budiwaty (UG Journal, 2022)
This research purposed to find out the types of taboo words and to describe the functions of the taboo words used in the Bad Boys For Life movie by Adil and Bilall. This Research used two theories, the theory from Battistella (2005) for analyzing the types of taboo words and the theory from Jay’ (1992) for analyzing the function of taboo words. The qualitative analysis method was used in thi s research. The result of the research showed that there were 4 types of taboo words that had been found. There were 193 data found in Bad Boys For Life movie namely: 10 data of Epithets, 21 Data of Profanity, 30 data of Vulgarity, and 132 data of Obscenity. For the function of taboo words, there were also 193 data were found, namely: 82 data of Anger and/or Frustration, 53 data of Descriptive – Evaluative, 5 data of Joking, 19 data of Surprise, and 34 data of Sarcastic Irony or Insults.